Determination of Translational and Rotational Diffusivities of Anisotropic Nanoparticles by Heterodyne Polarized and Depolarized Dynamic Light Scattering - Wu, Wenchang; Chittem, Pranay Kumar; Meißner, Frederik; Damm, Cornelia; Peukert, Wolfgang; Fröba, Andreas Paul (Journal of Physical Chemistry C, 2024)
This work presents the determination of translational diffusivities DT and rotational diffusivities DR of gold nanorods and silver nanocubes using polarized and depolarized dynamic light scattering. In combination with a heterodyne detection scheme, the signal-to-noise ratio of the analyzed correlation functions is significantly improved, which reduces the uncertainties in the determined mean lifetimes of the fluctuations studied and, thus, in the diffusivities. The heterodyne detection scheme also simplifies the data evaluation when homodyne conditions cannot be realized. For nanorods with aspect ratios ranging from 3.6 to 4.8, DT and DR were determined with average expanded uncertainties of (6 and 8) %. DT and DR increase with increasing temperature. In contrast, no concentration dependence of the diffusivities could be found for particle concentrations close to infinite dilution. Based on their values and a model in the literature, the length and width of the nanorods could be determined to be in agreement with the values from electron microscopy with deviations of (12 and 16) %. In this work, it was also demonstrated that dynamic light scattering is applicable for the determination of DT and DR for nanocubes with small anisotropy, with expanded uncertainties of (1.4 and 12) %. Due to the small anisotropic contribution to the scattered light, DR could only be obtained by depolarized dynamic light scattering. The experimental DR values are smaller than those calculated theoretically by the Stokes–Einstein–Debye relation, which, however, considers the nanocubes as equivalent sphere
Keywords: Colloids; Diffusion; Dynamic light scattering; Light; Nanoparticles